Facilities Renewal to Support the Revitalization of Nggirli Park in Srimulyo Village, Yogyakarta - Andrian Permana; Anisa Rahmawati, Nurwendah; Nina Restina, Widia; Oktaviani Ninat, Theresia; Nadya Ananta, I PT GD Surya; Malik, Dian; Muhammad Rizqia Rahman, Akmal; Lubis, Heri; Bayu Krisnawan, Dimas; Abu Rachman, Arief; Nuralika Pratiwi, Yurinda; Indra, Muhammad (ETHOS: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2024)
Nggirli Park is one of the tourist attractions in Srimulyo Village that is quite crowded and in demand by the community. During the COVID-19 pandemic, Nggirli Park had to be closed. After the pandemic, this park has not been able to revive. Revitalization is an effort to reconstruct the area so that it can improve the function of the previous area. The revitalization of Nggirli Park is one of the programs to support the revival of the tourism potential of Srimulyo Village and is expected to help accelerate revitalization after COVID-19. The Nggirli Park revitalization program is part of community service from Janabadra University, with activities including cleaning, renewing the facilities, greening, and rehabilitating the gazebo. This community service applies the participatory observation method. To obtain information from community leaders to determine the appropriate Nggirli Park revitalization program for the community, community service program students from Janabadra University conducted interviews with Bintaran Wetan Hamlet Chief and the Nggirli Park Management. The launch of several programs is expected to be able to support the growth of tourism in Srimulyo Village so that it becomes a sustainable tourism village.